2018
DOI: 10.1097/igc.0000000000001327
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Size at Magnetic Resonance Imaging Association With Lymph Node Metastasis and Lymphovascular Space Invasion in Resectable Cervical Cancer: A Multicenter Evaluation of Surgical Specimens

Abstract: ObjectiveTo determine whether gross tumor volume (GTV) and the maximum diameter of resectable cervical cancer at magnetic resonance imaging (MRI) could predict lymph node metastasis (LNM) and lymphovascular space invasion (LVSI).Materials and MethodsA total of 315 consecutive patients with cervical cancer were retrospectively identified. Gross tumor volume and the maximum diameter of tumor were evaluated on MRI. Univariate and multivariate logistic regression analyses were performed to determine whether tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
4
24
1
Order By: Relevance
“…Research has confirmed that tumor size can predict lymph node metastasis and lymph vascular space invasion in early-stage cervical cancer 30. Conversely, as T stage in TNM staging system can reflect tumor load in other solid tumors, the tumor size has been confirmed to be an independent prognostic factor for overall survival and distant metastasis-free survival in this study.…”
Section: Discussionsupporting
confidence: 57%
“…Research has confirmed that tumor size can predict lymph node metastasis and lymph vascular space invasion in early-stage cervical cancer 30. Conversely, as T stage in TNM staging system can reflect tumor load in other solid tumors, the tumor size has been confirmed to be an independent prognostic factor for overall survival and distant metastasis-free survival in this study.…”
Section: Discussionsupporting
confidence: 57%
“…Yang et al [31] determined found that the minimum apparent diffusion coe cient and the minimum apparent diffusion coe cient ratio were signi cantly lower in LVI-positive invasive cervical cancer than in LVI-negative invasive cervical cancer (0.772 ± 0.062 vs. 0.917 ± 0.052, p < 0.001, and 0.712 ± 0.078 × 10 −3 vs. 0.867 ± 0.099 × 10 −3 mm 2 /s, p < 0.001, respectively). Gross tumor volume [32] on MRI was also identi ed to be a possible independent risk factor for predicting LVSI (AUC = 0.700, p < 0.05). Recently, the use of radiomics based on magnetic resonance for predicting LVSI has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, most retrospective studies concerned patients treated by RT alone, and data on tumor size were not included, thus inducing significant bias. 8,9,33 Nevertheless, the associations between anemia and local recurrence and/or OS but also between hypoxia and radioresistance in animal models have led to the dogma that anemia increases tumor hypoxia in humans. 34 Concerning cervical cancer, a positive impact of anemia correction by RBC transfusions was described by Bush 12 in only one trial published in 1986.…”
Section: Discussionmentioning
confidence: 99%